2022
DOI: 10.3389/fpls.2022.918021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of real-time nutrient analysis of fertilized raspberry using petiole sap

Abstract: The time delay in receiving conventional tissue nutrient analysis results caused red raspberry (Rubus idaeus L.) growers to be interested in rapid sap tests to provide real-time results to guide immediate nutrient management practices. However, sap analysis has never been conducted in raspberry. The present work aimed to evaluate the relationship of petiole sap nitrate (NO3–), potassium (K+), and calcium (Ca2+) concentrations measured using compact ion meters and leaf tissue total nitrogen (TN), potassium (K),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These results are of considerable practical importance given the many research e.g., [18,20,21,31,34] and Extension publications e.g., [19,22] that have used these ISE meters or their predecessor (Cardy nitrate meter) for measurement of [NO 3 − ] to assist in N management of vegetable crops. In numerous studies, the combined use of these ISE meters and petiole sap analysis were presented as a crop N management package e.g., [30,32,33,41,42]. While a number of studies have evaluated the accuracy of these or similar ISE systems with a particular type of sample (petiole sap or soil solution) [18,19,31,35,[44][45][46], none of these considered how temperature affected the accuracy of measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are of considerable practical importance given the many research e.g., [18,20,21,31,34] and Extension publications e.g., [19,22] that have used these ISE meters or their predecessor (Cardy nitrate meter) for measurement of [NO 3 − ] to assist in N management of vegetable crops. In numerous studies, the combined use of these ISE meters and petiole sap analysis were presented as a crop N management package e.g., [30,32,33,41,42]. While a number of studies have evaluated the accuracy of these or similar ISE systems with a particular type of sample (petiole sap or soil solution) [18,19,31,35,[44][45][46], none of these considered how temperature affected the accuracy of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement may take place immediately following storage in a refrigerator, on samples obtained from plants and fertigation systems at very different ambient temperatures, or from soils subject to appreciable temperature variation. Given the strong and on-going interest in using ISE systems for on-farm measurement of [NO 3 − ], e.g., [13,18,19,22,23,29,33,41,42], there is a need to assess how sample temperature affects the accuracy of [NO 3 − ] measurement. In this study, the effects of sample temperature on two similar models of a commercially available ISE were examined.…”
Section: Of 12mentioning
confidence: 99%
“…The author showed that a high dose of nitrogen (178 kg N ha•ha −1 ) did not increase the yield compared with a low dose of N fertilizer (40 kg N ha•ha −1 ). The lack of effect of the dose of N on the yield and quality of fruit was also observed by scientists conducting an experiment with the red cultivar 'Meeker' in north-western Washington (USA) [48]. According to the authors, this could be related to the mineralization of nutrients in the soil and the use of nutrient reserves accumulated in the plant.…”
Section: Influence Of Fertilization On the Size And Quality Of Fruit ...mentioning
confidence: 93%